Экран, поглощающий направленное оптическое излучение - Мышкин В. Ф. Вячеслав Фёдорович; Цимбал В. Н.; Тихомиров И. А. Иван Арсентьевич; Моторин А. Н. Анатолий Николаевич; Целебровский А. И. Алексей Игоревич
опубл. 10.12.02